2012
DOI: 10.1074/jbc.m111.306209
|View full text |Cite
|
Sign up to set email alerts
|

Cell Division Cycle 7 Is a Novel Regulator of Transforming Growth Factor-β-induced Smooth Muscle Cell Differentiation

Abstract: Background: Cell differentiation and proliferation are regulated simultaneously during early development, but the underlying mechanisms remain largely unknown. Results: Cell division cycle 7 (Cdc7) regulates TGF-␤-induced smooth muscle cell differentiation. Conclusion: Cdc7 is likely a common factor regulating both cell proliferation and differentiation. Significance: Our data provide a novel mechanism governing the synchronized regulation of cell proliferation and differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…The present study together with our recently published results (20,37) provide a model for Cdc7 function in the initial and late phase of TGF-␤-induced SM differentiation, i.e. upon TGF-␤ stimulation, Smad3 is activated and translocated to nucleus where it binds to Cdc7 and Nkx2.5.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…The present study together with our recently published results (20,37) provide a model for Cdc7 function in the initial and late phase of TGF-␤-induced SM differentiation, i.e. upon TGF-␤ stimulation, Smad3 is activated and translocated to nucleus where it binds to Cdc7 and Nkx2.5.…”
Section: Discussionmentioning
confidence: 98%
“…TGF-␤ also regulates cell proliferation in different physiological contexts (8,(17)(18)(19). Our previous studies have shown that cell division cycle 7 (Cdc7), a cell cycle regulator facilitating initiation of DNA replication, regulates the initiation program of TGF-␤-induced SM differentiation via interaction with Smad3 while stimulating cell proliferation (20). It is unknown, however, whether Cdc7 plays a role in SM maturation.…”
Section: Vascular Smooth Muscle (Sm)mentioning
confidence: 99%
See 2 more Smart Citations
“…This explanation would be consistent with the inability of Cdc7 to rescue the mitotic growth defect of cdc7-90 yeast in the absence of Chiffon. A recent study has shown that Dbf4 knockdown has no effect on Cdc7-dependent induction of smooth muscle cell differentiation in murine cell lines, which is instead dependent on interactions between Cdc7 and the SMAD3 transcriptional modulator (92). Thus, there is a precedent for the ability of Cdc7 to function in specific developmental processes independently of Dbf4, potentially through interactions with other unrelated factors.…”
Section: Discussionmentioning
confidence: 99%